Homocysteine causes cerebrovascular leakage in mice - Lominadze, David (2005)
Elevated plasma homocysteine (Hcy) is associated with cerebrovascular disease and activates matrix metalloproteinases (MMPs), which lead to vascular remodeling that could disrupt the blood-brain barrier. To determine whether Hcy administration can increase brain microvascular leakage secondary to activation of MMPs, we examined pial venules by intravital video microscopy through a craniotomy in anesthetized mice. Bovine serum albumin labeled with fluorescein isothiocyanate (BSA-FITC) was injected into a carotid artery to measure extravenular leakage. Hcy (30 μM/total blood volume) was injected 10 min after FITC-BSA injection. Four groups of mice were examined: 1) wild type (WT) given vehicle; 2) WT given Hcy (WT + Hcy); 3) MMP-9 gene knockout given Hcy (MMP-9−/− + Hcy); and 4) MMP-9−/− with topical application of histamine (10(−4) M) (MMP-9−/− + histamine). In the WT + Hcy mice, leakage of FITC-BSA from pial venules was significantly (P < 0.05) greater than in the other groups. There was no significant leakage of pial microvessels in MMP-9−/− + Hcy mice. Increased cerebrovascular leakage in the MMP-9−/− + histamine group showed that microvascular permeability could still increase by a mechanism independent of MMP-9. Treatment of cultured mouse microvascular endothelial cells with 30 μM Hcy resulted in significantly greater F-actin formation than in control cells without Hcy. Treatment with a broad-range MMP inhibitor (GM-6001; 1 μM) ameliorated Hcy-induced F-actin formation. These data suggest that Hcy increases microvascular permeability, in part, through MMP-9 activation.